2022
DOI: 10.1177/15330338211068965
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Breast Cancer Patients Sensitive and Resistant to Chemotherapy: Looking for Overall Survival and Drug Resistance Biomarkers

Abstract: Worldwide breast cancer ranks first in mortality and incidence rates in women over 20 years old. Rather than one disease, breast cancer is a heterogeneous group of diseases that express distinct molecular profiles. Neoadjuvant chemotherapy is an important therapeutic strategy for breast cancer patients independently of their molecular subtype, with the drawback of resistance development. In addition, chemotherapy has adverse effects that combined with resistance could contribute to lower overall survival. Alth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 85 publications
2
16
0
Order By: Relevance
“…[ 12 ] Besides, another study reveals that KRT15 overexpression is associated with tumor metastasis in breast cancer patients. [ 17 ] In the present study, KRT15 protein expression was correlated with the occurrence of lymphovascular invasion and more advanced FIGO stage; meanwhile, KRT15 mRNA expression was correlated with the more advanced FIGO stage and marginally associated with the occurrence of stromal cervical invasion. Possible explanations could be that: KRT15 upregulation is associated with enhanced cancer stem cell property which exhibits a strong infiltration capacity; thus, KRT15 overexpression is linked with the occurrence of lymphovascular invasion and stromal cervical invasion in EC patients.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…[ 12 ] Besides, another study reveals that KRT15 overexpression is associated with tumor metastasis in breast cancer patients. [ 17 ] In the present study, KRT15 protein expression was correlated with the occurrence of lymphovascular invasion and more advanced FIGO stage; meanwhile, KRT15 mRNA expression was correlated with the more advanced FIGO stage and marginally associated with the occurrence of stromal cervical invasion. Possible explanations could be that: KRT15 upregulation is associated with enhanced cancer stem cell property which exhibits a strong infiltration capacity; thus, KRT15 overexpression is linked with the occurrence of lymphovascular invasion and stromal cervical invasion in EC patients.…”
Section: Discussionsupporting
confidence: 50%
“…[ 12 ] Differently, it is illustrated that KRT15 is downregulated in carcinoma tissue compared with normal tissue from breast cancer patients. [ 14 , 15 , 17 ] KRT15 expression discloses an opposite trend in breast cancer, which might be explained by that: The apoptosis and differentiation of KRT15 would be influenced by endocrine status, hence, we hypothesize that KRT15 expression in breast cancer might be affected by the hormonal environment (such as estrogen, progesterone, etc) [ 18 , 19 ] ; whereas, this speculation needs further investigation in the in vivo and in vitro studies. In the current study, it was discovered that KRT15 was higher in tumor tissue compared with adjacent tissue; meanwhile, it exhibited an acceptable capability in distinguishing tumor tissue from adjacent tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA-Seq data samples of breast cancer patients sensitive and resistant to neoadjuvant chemotherapy were downloaded from the GEO database, GSE162187 [ 114 ] and GSE163882 [ 115 ]. A total of 89 data samples sensitive to treatment and 154 data samples resistant to the treatment were used for downstream analysis.…”
Section: Methodsmentioning
confidence: 99%
“…It has been indicated that TUBB mediates cell cycle, epithelial-mesenchymal transition (EMT), proliferation, metastasis, and invasion in cutaneous melanoma, possibly through the downregulation of tumor suppressor miR-339-3p [ 14 ]. It has been shown recently that TUBB mRNA expression is upregulated in breast cancer patients resistant to chemotherapy [ 10 , 15 ]. Mutations in TUBB have been shown to demonstrate resistance to chemotherapy [ 16 , 17 ], in which the l240I mutation shows specific resistance to vincristine [ 18 ].…”
Section: Introductionmentioning
confidence: 99%